Equipartition in the hot-spots of 3C 123 - Hardcastle, M; Birkinshaw, M; Worrall, D (2002)
Chandra X-ray Observatory observations of the powerful, peculiar radio galaxy 3C 123 have resulted in an X-ray detection of the bright eastern hot-spot, with a 1-keV flux density of similar to 5 nJy. The X-ray flux and spectrum of the hot-spot axe consistent with the X-rays being inverse-Compton emission from the population of electrons responsible for the radio emission, if the magnetic fields in the hot-spot are close to their equipartition values. 3C 123 is thus the third radio galaxy to show direct evidence for equipartition in hot-spots.